A comparison study of the perfornance of the extreme value type 1 (EV1) and the rayleigh distribution in flood frequency analysis - Yaziz , Siti Roslindar (Penerbit UTM, 2006)
Flood frequency analysis is the statistical method of flood estimation which relates flood magnitude to the frequency of return period. The objective of flood frequency analysis is to establish a flood magnitude-return period relation by statistical analysis of measured streamflow data and to summarize it in a simple mathematical form using as few parameters as possible [1]. A procedure commonly used in flood frequency analysis consists of three important steps: (i) selection of the probability function to be fitted; (ii) estimation of its parameter, and (iii) testing its goodness-of-fit to the empirical distribution.